Peran Ulama dalam Kehidupan Sosial dan Politik Masyarakat Islam di Kecamatan Panyabungan Mandailing Natal - M. Ilham Nasution; Faisal Riza; Aulia Kamal (Najah Bestari, 2026)
Ulama have a very important function and role in teaching, guiding/directing and being role models for the people towards a better direction, so that deviations and errors in education are unlikely to occur. The purpose of this research is to determine the role of ulama, obstacles and efforts made by ulama in Panyabungan District, Mandailing Natal Regency in improving the development of Islamic religious education. This type of research is a type of field research, namely research on the role of ulama in development. Islamic Religious Education in Panyabungan District, with a phenomenological approach, namely a case study that studies humans as phenomena. This research shows that the role of ulama in providing Islamic religious education guidance in Panyabungan District has played an active role, but is not really responded to by the community. Ulama only provide recitations for the community. This activity is carried out once a week. The study did not go very smoothly. Meanwhile, for young people, there are no recitation activities being organized. The obstacle or obstacles faced by ulama in Panyabungan District in religious formation is the lack of information from the study leaders in conveying the study schedule to the community. Community economic factors are also quite serious obstacles in conveying religious knowledge. The efforts made by the ulama include holding recitation activities for fathers, mothers and children, delivering religious material at Friday sermons and providing religious advice for families.